2019
DOI: 10.1111/anu.13003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary zinc sources and levels on growth performance, tissue zinc retention and antioxidant response of juvenile common carp ( Cyprinus carpio var. Jian) fed diets containing phytic acid

Abstract: Plant protein‐based diets are widely used for common carp (Cyprinus carpio var. Jian). The plant source antagonist, such as phytate, negatively affects the bioavailability of trace minerals, but this aspect was not considered in previous studies on this species. A 10‐week growth trial was conducted to investigate the effects of inorganic Zinc (ZnSO4·7H2O, Zn‐S) and organic Zn (2‐hydroxy‐4‐(methylthio) butanoic Zinc, Zn‐M) on growth performance, Zn retention and antioxidant responses of common carp (initial wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Aquatic animals fed diets are probably to have evidently higher dietary zinc demand because of the existence of tricalcium phosphate and phytic acid obtained from feed ingredients, which can obstruct zinc in the feed and influence the bioavailability of zinc for aquaculture (Denstadli et al, 2006;Laining et al, 2010;Liang et al, 2020). Compared with previous study, the zinc requirement (60.03-61.27 mg Zn/kg) for soft-shelled turtle was higher than that in previous work (42-46 mg Zn/kg) (Huang et al, 2010).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Aquatic animals fed diets are probably to have evidently higher dietary zinc demand because of the existence of tricalcium phosphate and phytic acid obtained from feed ingredients, which can obstruct zinc in the feed and influence the bioavailability of zinc for aquaculture (Denstadli et al, 2006;Laining et al, 2010;Liang et al, 2020). Compared with previous study, the zinc requirement (60.03-61.27 mg Zn/kg) for soft-shelled turtle was higher than that in previous work (42-46 mg Zn/kg) (Huang et al, 2010).…”
Section: Discussionmentioning
confidence: 56%
“…Opposite to our result, dietary Zn inclusions had no evident impact on hepatosomatic index (HSI) or viscerosomatic index (VSI) of grass carp (Ctenopharyngodon idella) (Liang et al, 2012), common carp (Cyprinus carpio var. Jian) (Liang et al, 2020) and Jian carp (Cyprinus carpio var. Jian) (Tan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The intestine is the primary organ for absorbing mineral elements derived from diet. It was demonstrated that, compared to the inorganic Zn source (ZnSO 4 ), the dietary organic Zn source (2-hydroxy-4-(methylthio) butanoic Zn) and nano Zn promoted more Zn accumulation in the intestine of fish [ 9 , 10 ]. Zn transport is mainly regulated by ZnTs, ZIPs, and MTF1 [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zn sulphate (ZnSO 4 ) is traditionally used in fish feeds, but it suffers from low bioavailability and poor absorption efficiency [ 3 , 8 ]. Studies demonstrated that dietary organic Zn source (2-hydroxy-4-(methylthio) butanoic Zn) or nano-Zn addition promotes growth performance and intestinal Zn accumulation of fish compared to the inorganic Zn source (ZnSO 4 ) [ 9 , 10 ]. Therefore, compared with inorganic Zn sources, organic and nanoform Zn have higher bioavailability, making them effective alternatives to inorganic Zn in aquafeeds [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%